2011
DOI: 10.1063/1.3563578
|View full text |Cite
|
Sign up to set email alerts
|

Co2MnGe-based current-perpendicular-to-the-plane giant-magnetoresistance spin-valve sensors for recording head applications

Abstract: Magnetic and magnetotransport properties of current-perpendicular-to-the-plane (CPP) giant-magnetoresistance (GMR) spin-valve sensors containing the Heusler alloy Co2MnGe are presented. The geometrical and head integration constraints which exist for recording head applications are discussed and dictate various design compromises which determine the final device properties. Here we show that even for small total sensor thicknesses 400 Å and anneal temperatures < 250 °C we can obtain CPP-GMR signal level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(36 citation statements)
references
References 24 publications
1
34
0
1
Order By: Relevance
“…24 Fe 0. 16 Si 0.84 ) electrodes through the Fe composition (β ) dependence of the TMR ratio of CMFS MTJs that have Co 2 (Mn α Fe β )Si 0.84 electrodes with a constant (α + β ) value of 1.40 (series-B CMFS MTJs) [47]. These TMR ratios are significantly higher than those obtained for CMS MTJs that have Mn-rich CMS electrodes [10].…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…24 Fe 0. 16 Si 0.84 ) electrodes through the Fe composition (β ) dependence of the TMR ratio of CMFS MTJs that have Co 2 (Mn α Fe β )Si 0.84 electrodes with a constant (α + β ) value of 1.40 (series-B CMFS MTJs) [47]. These TMR ratios are significantly higher than those obtained for CMS MTJs that have Mn-rich CMS electrodes [10].…”
Section: Introductionmentioning
confidence: 65%
“…The enhancement in the TMR ratio for the MTJ with Co 2 Mn 1.24 Fe 0. 16 Si 0.84 electrodes (δ = 1.40) of up to 2610% at 4.2 K and μ s being close to its half-metallic value can be explained by the half-metallicity being retained for δ-rich CMFS, with a small amount of Fe replacing Mn, wherein residual Co Mn/Fe antisites are further suppressed by the δ-rich composition. Section IV summarizes our results and concludes the paper.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…11 Such a high MR output in a low resistance device has already satisfied the MR performance required for the areal density of 2 Tbit/in 2 according to the simulation by Takagishi et al 7 However, all of these high MR outputs have only been demonstrated for the epitaxial CPP-GMR pseudospin-valves (PSVs) grown on unpractical MgO single crystalline substrates, which are too expensive for mass production and incompatible with the current semiconductor industry processes. On the other hand, for industrial viability, polycrystalline CPP-GMR devices that were grown on thermal-oxidized Si substrate have been used, [12][13][14] but unfortunately, the MR output of polycrystalline devices is much lower than those of epitaxial devices that were grown on MgO substrates. The existence of grain boundary and inferior layer roughness is considered to be the possible reasons for such a large discrepancy of MR outputs between polycrystalline and single crystalline (epitaxial) devices.…”
mentioning
confidence: 99%
“…These alloys have been extensively applied to spintronic devices, including magnetic tunnel junctions (MTJs) [13][14][15][16][17][18] and giant magnetoresistance (GMR) devices. [19][20][21][22][23] We recently demonstrated high tunnel magnetoresistance (TMR) ratios of up to 1995% at 4.2 K and up to 354% at 290 K in Co 2 MnSi/MgO/Co 2 MnSi MTJs with Mn-rich Co 2 MnSi electrodes. 18 The observed high TMR ratios for MTJs with Mn-rich Co 2 MnSi electrodes are attributed to suppressed Co Mn antisites, which leads to the enhanced half-metallicity through a reduced density of minority-spin in-gap states around E F .…”
Section: Effect Of Cofe Insertion In Co 2 Mnsi/cofe/n-gaas Junctions mentioning
confidence: 99%